Microwave-assisted synthesis of chromeno[3,4-b]xanthones and (benzo[c]cromenyl)chromones - Albuquerque, Hélio (2017)
Two series of novel propargyloxychromones were designed and synthesized. Both chromone derivatives were used as substrates in MW-assisted intramolecular Diels-Alder reactions, affording chromeno[3,4-b]xanthones and (benzo[c]chromenyl)chromones. This is the first report involving chromone derivatives in intramolecular Diels-Alder reactions for the synthesis of new oxygen heterocycles, namely xanthones and flavones.